Proofs involving Conjunctions and Biconditionals
Note: A lot of the first few problems are of the same type. Skipped the similar ones.
1.
-->
Given
∀x(P(x) ∧ Q(x))
Goal
∀x P(x) ∧ ∀x Q(x)
Let ∀x(P(x) ∧ Q(x))
So for an arbitrary y, P(y) ∧ Q(y).
Hence, P(y). So ∀x P(x) is true. So is ∀x Q(x)
So, for arbitrary x, P(x) and Q(x) are true.
Hence,
∀x P(x) ∧ ∀x Q(x)
<--
Given
∀x P(x) ∧ ∀x Q(x)
Goal
∀x(P(x) ∧ Q(x))
Let ∀x P(x) ∧ ∀x Q(x)
For arbitrary y, ∀y P(y) ∧ ∀y Q(y)
Since P(y), and also Q(y), hence P(y) ∧ Q(y) is also true.
Since y was arbitrary, P(x) ∧ Q(x) is true for any value of x.
Hence, ∀x(P(x) ∧ Q(x))
2.
Givens
A ⊆ B
A ⊆ C
Goal
A ⊆ B ∩ C
Revised
Givens
x ∈ A
x ∈ A -> x ∈ B
x ∈ A -> x ∈ C
Goal
x ∈ B
x ∈ C
From the givens, x ∈ A is true. Hence, so is x ∈ B (first goal) and x ∈ C (second goal)
3.
Givens
x ∈ A -> x ∈ B
Goal
x ∈ C \ B ⊆ x ∈ C \ A
Let x be an arbitrary element of an arbitrary set C.
Revised Givens
x ∈ A -> x ∈ B
x ∈ C ∧ x ∉ B
Goal
x ∈ C \ A
The first given can be expressed as (modus tollens)
x ∉ B -> x ∉ A
x ∈ C
x ∉ B
Goals
x ∈ C
x ∉ A
From the givens,
x ∉ B, hence x ∉ A as well, which is one of the goals
From the second given, x ∈ C, which is the second goal.
9.
Given
x and y are odd integers
Goal
xy is odd
Since x and y are odd integers, they can be expressed as
x = 2k +1
y = 2m + 1,
where k and m are integers
Hence, xy = (2k + 1) (2m + 1)
= 2(2km + k + m) + 1
2km + k + m is an integers, and 2(2km + k + m) is even. Hence, 2(2km + k + m) + 1 is odd.
10.
n3 is even iff n is even
-->
We'll prove by contradiction.
Givens
n3 is even
n is odd
Goal
Contradiction
n3 is even, so
n3 = 2k, where k is an integer.
n is odd, so n = 2m + 1, m being an integer.
Hence, (2k)3 = (2m + 1)3
or,
2.4k3 = 2(4m3 + 6m2 + 3m) + 1
which is impossible as the number of the left is even, while the one on the right is odd.
Hence, n has to be even if n3 is odd.
<---
Given
n is even
n3 is odd
Goal
Contradiction
n is even, so n = 2k, k being an integer
n3 is odd, so n3 = 2m + 1, m being an integer
Hence, (2k)3 = 2m + 1
=> 2(4.k3) = 2m + 1
Which is impossible, as the left expression evaluates to an even integer, while the right one to an odd integer.
Hence, n3 is even when n is even.
Combining the two, n3 is even iff n is even.
11.
(a) The same 'k' cannot be chosen, as it translates that m = n+1, which is not an assumption that is given.
(b) The theorem is incorrect.
Counterexample - m = 4, n =7
No comments:
Post a Comment